2005
DOI: 10.1007/s10681-005-0548-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of different PCR-based marker systems in assessing genetic diversity among winter rye (Secale cereale L.) inbred lines

Abstract: The aim of this study was to investigate the efficiency of ISSR, SSR, and SAMPL marker systems in detecting genetic polymorphism among 30 winter rye inbred lines and to compare the results of cluster analysis performed on data from these marker systems using different statistical methods and coefficients. Each marker system was able to discriminate among the materials analyzed with the lowest value of average genetic similarity (GS) obtained with ISSR markers (0.2888) and the highest with SAMPLs (0.5381). EST-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 12 publications
5
36
1
Order By: Relevance
“…Diversity studies by Warwick et al (2008) and Ofori et al (2008) also revealed essentially the same patterns of variation. Similar patterns can also be found in other openpollinated crops like maize (Zea mays L.; Warburton et al 2008), buckwheat (Fagopyrum esculentum Moench; Iwata et al 2005) and winter rye (Secale cereale L.; Bolibok et al 2005).…”
Section: Genetic Structuresupporting
confidence: 62%
“…Diversity studies by Warwick et al (2008) and Ofori et al (2008) also revealed essentially the same patterns of variation. Similar patterns can also be found in other openpollinated crops like maize (Zea mays L.; Warburton et al 2008), buckwheat (Fagopyrum esculentum Moench; Iwata et al 2005) and winter rye (Secale cereale L.; Bolibok et al 2005).…”
Section: Genetic Structuresupporting
confidence: 62%
“…The bulk method is a good tool for this approach due to the high degree of polymorphism observed in this study. Use of different markers are essential to obtain more reliable genetic relationships (Bolibok et al 2005). The relationships obtained simultaneously using RAPD and ISSR markers are more accurate and the bootstrap values are higher than using one kind of marker.…”
Section: Genetic Relationships Among Secale Taxamentioning
confidence: 99%
“…A total of 264 SSR primer pairs were used. The PCR reactions, electrophoresis and visualization were performed as described by Bolibok et al [22]. ISSR and SAMPL analyses were done as described previously [22].…”
Section: Molecular Marker Analysesmentioning
confidence: 99%
“…The PCR reactions, electrophoresis and visualization were performed as described by Bolibok et al [22]. ISSR and SAMPL analyses were done as described previously [22]. ISSR markers were designated ISSRx_n, where x is the primer number, and n is the product length.…”
Section: Molecular Marker Analysesmentioning
confidence: 99%